Efficacy and safety of Jintiange in the treatment of osteoporosis: a systematic review and meta-analysis - Man, Yicong; Na, Junfu; Wang, Hongxu; Lan, Fang; Yu, Liying (Frontiers in Pharmacology, 2025)
ObjectiveTo evaluate the efficacy and safety of Jintiange in osteoporosis treatment via systematic review and meta-analysis, thereby presenting more supporting evidence.MethodsUp to 27 October 2024, PubMed, Web of Science, Cochrane Library, Embase, China National Knowledge Infrastructure (CNKI), and Wanfang were searched for studies on the use of Jintiange/artificial tiger bone powder in osteoporosis treatment. Studies were selected based on predefined eligibility criteria. Outcome measures encompassed bone mineral density (BMD), pain scores, adverse event (AE), fracture incidence, serum calcium, and phosphorus concentrations, as well as bone resorption and formation markers.ResultsThis study included 18 studies involving 21 trials on 2,580 patients (1,303 in the Jintiange group and 1,277 in the control group). A pooled analysis demonstrated that, in comparison to the control group, the Jintenge group achieved significantly greater improvements in BMD at various anatomical sites, including the lumbar spine (SMD = 0.52), femoral neck (SMD = 0.31), greater trochanter (SMD = 0.59), and Ward’s triangle (SMD = 0.94). In addition, the Jintenge group exhibited a greater reduction in Visual Analogue Scale (VAS) scores (SMD = −0.87). No significant differences were observed between the two groups in terms of AEs or incidence of fractures. The level of bone Gla protein (BGP) was significantly higher in the Jintenge group compared with the control group (SMD = 1.28), whereas there were insignificant intergroup differences in serum calcium and phosphorus concentrations or changes in the type I collagen carboxy-terminal peptide (CTX). Sensitivity analysis revealed inconsistent results of Procollagen type I N-terminal propeptide (PINP) and bone alkaline phosphatase (BALP).ConclusionJintiange possibly improves BMD and alleviates pain in osteoporosis patients, with a favorable safety profile. Prolonged treatment duration (exceeding 6 months) yields greater therapeutic benefit than shorter courses, and the combination of Jintiange with standard therapies demonstrates superior efficacy relative to Jintiange alone. However, in consideration of the limitations of the present study, further high-quality investigations are necessitated to strengthen the evidence base and to elucidate the long-term efficacy, safety, and impact of this agent on fracture incidence.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42025630527.